Answer:
less then 3
Step-by-step explanation:
The definition is pretty simple:
![(f+g)(x) = f(x)+g(x)](https://tex.z-dn.net/?f=%20%28f%2Bg%29%28x%29%20%3D%20f%28x%29%2Bg%28x%29%20)
So, we only have to sum the expressions:
![f(x)+g(x) = 2x+4 - \dfrac{1}{5}x-3 = \dfrac{9}{5}x+1](https://tex.z-dn.net/?f=%20f%28x%29%2Bg%28x%29%20%3D%202x%2B4%20-%20%5Cdfrac%7B1%7D%7B5%7Dx-3%20%3D%20%5Cdfrac%7B9%7D%7B5%7Dx%2B1%20)
The answer is C hope this helps
Answer:
Step-by-step explanation:
Angles on a straight line add up to 180 so:
180-110 = 70
As this is an isosceles triangle,
y must be 70.
We know y is 70 and there are 2y and one x. A triangle also adds up to 180.
This means:
2y+x = 180
2(70)+x = 180
140+x = 180
x = 40
x = 40 y = 70
Answer:
95891769
Step-by-step explanation:
This is extract from a brain teaser exercise in which sequence is formed to identify the numbers. In this brain teaser we have made combinations of different numbers which lead to the correct answer. The two correct forms of number are given which are used as a base for determining the correct answer.